Perancangan Compact Booth untuk Produk Pakaian dan Aksesoris Pada Indoor Market - Wijaya, Felicia; Kusumarini, Yusita; Rizqy, M. Taufan (Intra, 2016)
Fashion and accessories is the type of industry which is a prime mover in the development of national creative industrywith various diversity type. It’s shown with various types of exhibition eventes such as bazaar market.Therefore needed booth which accommodate the function of the display and the module settings for any products and practical system that can provide easy installation and mobilization module setings. The design method using the methods of David Kelley with the following stages discovery, interpretation, ideation, experimentation, dan evolution. Compact design booth is an innovation display system for interior of exhibition space. The advantages of this design is a flexible display system with various conditions on the showroom as product type, the size of the stand and the diversity of the settings for the display module forms. In addition to the use of colors and finishes can be customized with the branding companies so that they can show and supports up a brand.